Radiologische Diagnostik spinaler Tumoren - Wolf, Marcel; Kloth, Jost; Hähnel, Stefan; Rehnitz, Christoph; Wiedenhöfer, Bernd; Weber, Marc-André (Der Orthopäde, 2012)
Intradural tumors are classified into extramedullary and intramedullary localization. A distinct attribution to one of these compartments is essential for finding the appropriate diagnosis. In the radiological evaluation of intradural tumors magnetic resonance imaging (MRI) is the most important method and in contrast to osseous spinal tumors, radiography and computed tomography are of minor importance. According to the globally established WHO grading system, tumors of the central nervous system are histopathologically classified into four grades. Through grades I to IV malignancy and proliferative activity increase. Prognosis is inversely correlated to the WHO grade. Intradural tumors are generally treated by neurosurgeons. Besides neurological symptoms intradural tumors often cause spinal malpositioning. Thus knowledge of the most frequent intradural tumors and their characteristic magnetic resonance findings are important in the orthopedic practice.